2004
DOI: 10.1038/sj.ejcn.1602049
|View full text |Cite
|
Sign up to set email alerts
|

Body water distribution in severe obesity and its assessment from eight-polar bioelectrical impedance analysis

Abstract: Objective: To measure body water distribution and to evaluate the accuracy of eight-polar bioelectrical impedance analysis (BIA) for the assessment of total body water (TBW) and extracellular water (ECW) in severe obesity. Design: Cross-sectional study. Setting: Obesity clinic. Subjects: In all, 75 women aged 18-66 y, 25 with body mass index (BMI) between 19.1 and 29.9 kg/m 2 (ie not obese), 25 with BMI between 30.0 and 39.9 kg/m 2 (ie class I and II obese), and 25 with BMI between 40.0 and 48.2 kg/m 2 (ie cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
1
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 16 publications
3
98
1
9
Order By: Relevance
“…The eight-polar BIA has been shown to give accurate estimates of body components in different populations without the need for population-specific algorithms. [28][29][30] This method is practical in large epidemiological studies with limited time for examination of each subject. 28,29 The outputs of InBody 3.0 are based on segmental 28,29 Resistance of arms, trunk and legs was measured at frequencies of 5, 50, 250 and 500 kHz with the subject standing barefoot in light clothing on the four foot electrodes on the platform of the analyzer and gripping the two palm and thumb electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight-polar BIA has been shown to give accurate estimates of body components in different populations without the need for population-specific algorithms. [28][29][30] This method is practical in large epidemiological studies with limited time for examination of each subject. 28,29 The outputs of InBody 3.0 are based on segmental 28,29 Resistance of arms, trunk and legs was measured at frequencies of 5, 50, 250 and 500 kHz with the subject standing barefoot in light clothing on the four foot electrodes on the platform of the analyzer and gripping the two palm and thumb electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the sequence of measurements has been described. [28][29][30] Isometric grip strength of the dominating hand was tested by a Newtest Grip Force dynamometer (Newtest Oy, Oulu, Finland). The maximum value of three squeezes was used in analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The lower accuracy of BIA in the obese might be explained by the body water distribution changing with the increase of body fat. The obese have a higher relative amount of extracelluar water than lean individuals (Wang and Pierson Jr, 1976;Sartorio et al, 2005;Ritz et al, 2008). BIA impedance will therefore be lower in the obese at a given FFM and body weight and the general BIA equation will overestimate the TBW and FFM (Deurenberg et al, 1991).…”
Section: Development Of Bia Equationsmentioning
confidence: 99%
“…We have shown that eight-polar BIA offers accurate estimates of total body water, extracellular water, FFM and appendicular LTM in healthy and obese subjects (Bedogni et al, 2002;Malavolti et al, 2003;Sartorio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%